PEMBENTUKAN KELOMPOK SEL BAGI SUKU SUNDA DI GUNUNG PUNTANG SEBAGAI WADAH UNTUK PERTUMBUHAN ROHANI - Dharmawan, Rinaldi; Simanjuntak, Ferry; Sodikdiana, Martinus Hartono; Mongkau, Hendry; Novita, Tricia (ABDI WINA JURNAL PENGABDIAN KEPADA MASYARAKAT, 2023)
The cell group is an important forum in the formation of the congregation in a church. Through this community, the congregation can be more accessible because the scope of the cell group is smaller. The need for a cell group’s community is also felt by believers who come from the Sundanese tribe and live around Mount Puntang. It is for this reason that our team decided to facilitate a cell community forum for the Sundanese tribe, most of them are from Mount Puntang.